2014
DOI: 10.1684/ejd.2014.2367
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive skin in Brazil and Russia: An epidemiological and comparative approach

Abstract: Sensitive skin in Brazil and Russia: An epidemiological and comparative approachBackground: Sensitive skin is characterized by the occurrence of sensations of tingling, prickling, heat, burning, pain or itching and, on occasion, erythema, in response to multiple physical, chemical or hormonal factors that do not have irritant properties by themselves. Objective: We chose here to evaluate sensitive skin in two countries with very different populations, climates and lifestyles: Russia and Brazil. Method: Represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 25 publications
(33 reference statements)
2
48
0
2
Order By: Relevance
“…In particular, some studies included only women, 10 whereas other studies used quota methods and included as many men as women. 7,12,13,22 Some linguistic or cultural differences could also explain these variations and differences in the distribution of phototypes. For example, SS affected 66% of women and 51% of men in a recent study of 5000 persons.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, some studies included only women, 10 whereas other studies used quota methods and included as many men as women. 7,12,13,22 Some linguistic or cultural differences could also explain these variations and differences in the distribution of phototypes. For example, SS affected 66% of women and 51% of men in a recent study of 5000 persons.…”
Section: Discussionmentioning
confidence: 99%
“…Although the diagnosis of this condition is made by the patient itself, not by the physician, the assessment of sensitive skin is related to the declarations of the patient and this is why there are many studies on sensitive skin using surveys. The first epidemiological study of sensitive skin was conducted in the United Kingdom in 2001; then, studies were conducted in many countries throughout the world, including Belgium, China, France, Germany, Greece, Italy, Portugal, Spain, Switzerland, the United States of America, Brazil, Japan and Russia . All these studies used similar methodologies that were based on surveys of samples of the population aged 15 years and older but were not always performed in accordance with representative sampling; relevant information collected included gender, age, head of household's occupation, type of geographical area (metropolis, town, countryside) and region.…”
Section: Introductionmentioning
confidence: 99%
“…The first epidemiological study of sensitive skin was conducted in the United Kingdom in 2001 7 ; then, studies were conducted in many countries throughout the world, including Belgium, China, France, Germany, Greece, Italy, Portugal, Spain, Switzerland, the United States of America, Brazil, Japan and Russia. [8][9][10][11][12][13][14][15] All these studies used similar methodologies that were based on surveys of samples of the population aged 15 years and older but were not always performed in accordance with representative sampling; relevant information collected included gender, age, head of household's occupation, type of geographical area (metropolis, town, countryside) and region. The relatively low nonresponse rate to the question 'Do you have sensitive skin?'…”
Section: Introductionmentioning
confidence: 99%
“…Although there are currently limited data on the perceived prevalence of fragile skin in general adult populations, previous studies have evaluated the prevalence of reactive (sensitive) skin in individuals from a range of different populations, including the UK,18 France,19 Europe,20 Japan,21 Brazil and Russia,22 and the USA 23. Individuals reported a high prevalence of perceived reactive skin in these studies and, in general, reactive skin appeared to be reported more frequently in females than in males 24.…”
Section: Discussionmentioning
confidence: 99%